(untitled) (Homoeopathy for All, 2023)
Migraine causes a significant illness to the sufferers and it is more prevalent among women than men. Homoeopathic medicines help in reducing the intensity and frequency of the migraine attack. This article presents indications of commonly indicated homoeopathic medicines for migraine with their differential indications.